Experimental Evaluation of Hydraulic Performance of Outlet Structures with Baffle Blocks under Super critical Flows - Eloubaidy, Aziz F.; Maatoq, J. A.; Ghazali, Abdul Halim (Universiti Putra Malaysia Press, 2001)
The design of outlet transition in field irrigation system requires the flow attaining a uniform velocity at the end of such structures. In addition, super critical flow condition requires maximizing the dissipation of hydraulic energy possessed by the flowing water to hold its erosion capacity to a minimum. Floor baffle blocks incorporated in the outlet transition are useful for the above objectives. This laboratory investigation attempts to evaluate the effects of the relative sizes and arrangements of different types of baffle blocks on hydraulic performances of outlet transition of different configurations operating at super critical flow conditions. Dimensional analysis techniques were used to develop dimensionless ratios describing the geometry and the flow within an outlet transition containing certain types of appurtenance structures. The solution was evaluated in the laboratory with respect to measurable elements of the flow to achieve standardization and general evaluation of the effectiveness of the different types of baffle blocks. The results are presented in the form of dimensionless plots, which show the variation of the ratios developed earlier, with the controlled variation of Froude numbers. Expanding channel outlet transitions of straight-wall type of angle 10 0 , 20 0 and 30 o with two expansion ratios of 4 and 6 were tested with and without floor baffles. The outlets with baffles are generally found to be effective in creating optimum flow conditions than the plain outlets. The use of baffles also resulted in higher dissipation of energy within the outlets, with baffles having curved upstream edge (in plan) dissipated up to 42.7% more energy than the plain outlets.